PENGARUH PENEMPATAN KARYAWAN TERHADAP KINERJA KARYAWAN MELALUI MOTIVASI PADA PT BANK MUAMALAT INDONESIA, TBK CABANG JEMBER - Rochmah, Safrina Hafifatur (BISMA: Jurnal Bisnis dan Manajemen, 2017)
Abstract:This study aimed to analyze the dimensions of the employee work placement (promotion, transfer, and demotion) on motivation and employee performance, and to analyze the effect of motivation on employee performance. The sample consisted of 39 (thirty nine) respondents. Data were analyzed using path analysis. Results show that the total effect of the promotion variable on motivation is 0.618 or 61.8%. The total effect of the mutation on motivation is 0.003 or 0.3%. The total effect of demotion variable on motivation is 0.125 or 12.5%. The total effect of the promotion variable on employee performance is 0.687 or 68.7%. The total effect of mutation on employee performance is 0.012 or 1.2%, the total effect of demotion variable on employee performance is -0.038 or -3.8%, and the total effect of motivation variable on employee performance is 0.685 or 68.5%. Keywords: Promotion, Transfer, Demotion, Motivation, and Employee Performance.